Home education - Beck, Christian W. (Managing global transitions, 2006)
Home Education seems to be a successful way to educate. Academic results and socialization processes in home education are promising. Already home education is global, home educators everywhere educate their children themselves without schools. They develop new forms of local and international co-operation. Is home education an impulse to a renewing of modern education? Is home education globalization otherwise?
Keywords: izobraževalna politika; vzgoja in izobraževanje doma; zasebno poučevanje; pedagogika; pedagogy; globalizacija; globalization